Evaluasi Efektivitas Kinerja Instalasi Pengolahan Air Limbah Terhadap Effluent Limbah Cair Industri PT X - Elvina Rosita Anggraini; Aussie Amalia (Jurnal Serambi Engineering, 2024)
PT X's office and courier activities generate domestic wastewater on a daily basis. The activity comes from domestic activities and support activities such as vehicle washing, maintenance of equipment utilities, mopping and equipment washing. Wastewater has a negative impact on the environment and society if not properly managed. This research was conducted on the wastewater of PT X in March 2023 and the parameters to be tested were at the inlet and outlet points of the WWTP. The aim of this study is to determine the effect of the effluent treatment efficiency (%) on the ammonia and total coliform levels at the inlet and outlet of the PT X WWTP, which have exceeded the quality standard threshold. The methodology used is a quantitative descriptive method, namely by attaching laboratory test results in the form of numbers and using the Soeparman and Suparmin effectiveness formula. The results of calculating the effectiveness of reducing ammonia levels by 0% with ineffective information and the results of calculating the effectiveness of reducing total coliform levels by 0.98% with ineffective information. So the result of this study is that the ammonia levels at the inlet and outlet and the total coliform levels at the inlet of the effluent in the WWTP did not meet the required quality standards, which proves that the WWTP treatment system at PT X was not operating optimally.